Kinetics and dynamics of cyclosporine A in three hepatic cell culture systems. Issue 1 (25th December 2015) - Bellwon, P.; Truisi, G.L.; Bois, F.Y.; Wilmes, A.; Schmidt, T.; Savary, C.C.; Parmentier, C.; Hewitt, P.G.; Schmal, O.; Josse, R.; Richert, L.; Guillouzo, A.; et al.
Highlights: Kinetics of cyclosporine A were analyzed in 3 liver cell models over a 14-day period. Sandwich primary rat and human hepatocytes and HepaRG cells were compared. The cyclophilin B was produced and CsA-induced secreted in all cell models. CsA biotransformation was higher in human liver cells than in rat hepatocytes. Metabolic clearances were 12–14-fold higher in HepaRG cells than in primary hepatocytes. Abstract: In vitro experiments have a high potential to improve current chemical safety assessment and reduce the number of animals used. However, most studies conduct hazard assessment alone, largely ignoring exposure and kinetic parameters. Therefore, in this study the kinetics of cyclosporine A (CsA) and the dynamics of CsA-induced cyclophilin B (Cyp-B) secretion were investigated in three widely used hepatic in vitro models: primary rat hepatocytes (PRH), primary human hepatocytes (PHH) and HepaRG cells. Cells were exposed daily to CsA for up to 14 days. CsA in cells and culture media was quantified by LC-MS/MS and used for pharmacokinetic modeling. Cyp-B was quantified by western blot analysis in cells and media. All cell systems took up CsA rapidly from the medium after initial exposure and all showed a time- and concentration-dependent Cyp-B cellular depletion and extracellular secretion. Only in PRH an accumulation of CsA over 14 days repeated exposure was observed. Donor-specific effects in CsA clearance were observed in the PHH model and both PHH and HepaRG cells significantly metabolized CsA, with no bioaccumulation being observed after repeated exposure. The developed kinetic models are described in detail and show that all models under-predict the in vivo hepatic clearance of CsA, but to different extents with 27-, 24- and 2-fold for PRH, PHH and HepaRG cells, respectively. This study highlights the need for more attention to kinetics in in vitro studies.